How Animals Care for Their Babies - Hirschland, Roger B.; Nang ChanYeema (Washington, D.C, USA The National Geographical Society, 1987)
Depicts different kinds of parental behavior among a variety of animals, including the trumpeter swan, mountain goat, and baboon.
Keywords: Juvenile Nonfiction